2021
DOI: 10.3892/ol.2021.12995
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence on laparoscopic vs. open resection for gastric stromal tumours (Review)

Abstract: Although the use of laparoscopic surgery is increasing, controversy still surrounds its application for malignant conditions. Gastrointestinal stromal tumours (GISTs) are less demanding in terms of lymphadenectomy, meaning that laparoscopic resection might have a more defined benefit when compared with open resection. To the best of our knowledge, no randomized study exists that compares the laparoscopic and open resection of GISTs. The current study aimed to examine the relevant literature by means of a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In previous studies, laparoscopic resection for GIST was reported to be safe, feasible, cost-effective, and superior to open resection [84][85][86]. Additionally, it is reported that several treatment methods using ESD techniques, such as submucosal tunneling endoscopic resection (STER), endoscopic full-thickness resection, laparoscopic endoscopic cooperative surgery (LECS), and non-exposed endoscopic wall-inversion surgery (NEWS), and a combined laparoscopic and endoscopic approach for neoplasia with a non-exposure technique (CLEAN-NET) have shown good clinical outcomes [87][88][89][90].…”
Section: Treatmentmentioning
confidence: 99%
“…In previous studies, laparoscopic resection for GIST was reported to be safe, feasible, cost-effective, and superior to open resection [84][85][86]. Additionally, it is reported that several treatment methods using ESD techniques, such as submucosal tunneling endoscopic resection (STER), endoscopic full-thickness resection, laparoscopic endoscopic cooperative surgery (LECS), and non-exposed endoscopic wall-inversion surgery (NEWS), and a combined laparoscopic and endoscopic approach for neoplasia with a non-exposure technique (CLEAN-NET) have shown good clinical outcomes [87][88][89][90].…”
Section: Treatmentmentioning
confidence: 99%
“…Currently, the preferred treatment for GIST patients is surgical resection, with the goals of obtaining R0 margins, avoiding intraoperative tumour rupture and maximising preservation of organ function [ 3 , 4 ]. Nevertheless, a growing number of studies have found that direct surgical resection is difficult for patients with specific sites (oesophagogastric junction, low rectum, duodenum) and large tumour diameters [ 5 , 6 ]. Recently, imatinib, a small molecule tyrosine kinase inhibitor (TKI), has been widely used as an adjuvant therapy for GIST patients after surgery as it can inhibit cell growth and promote apoptosis by blocking tyrosine kinase [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%